BHAJI ON THE BEACH: HYBRID IDENTITY AND POPULAR DISCOURSES IN BRITISH DIASPORIC CINEMA - Valančiūnas, Deimantas (Literatūra, 2012)
Gurinder Chadha is a British South Asian diasporic director who attained international acclaim releasing films Bend it like Beckham (2002) and Bride and Prejudice (2004). However, her first feature film Bhaji on the Beach (1993) is one of the finest examples of British diasporic films. Released in the sensitive post-Thatcheric era, it investigates the complex issues of gender relations, racism, domestic violence, and hybridity in the diasporic environment. The film director also emphasizes different ideological formations which are produced in, and disseminated through popular discourses. Therefore this article explores the ways identity is constructed through various ideological and nationalistic discourses embedded in the popular culture, particularly in Bollywood and imperial British cinema and heritage films. Such popular discourses are seen as major ideological forces used to establish monolithic and fixed identity, creating disruptions and crises when it clashes with contemporary hybrid British culture.